Pengaruh Pengetahuan dan Promosi Terhadap Minat Menabung Tabungan Haji Di Bank Syariah - Muliyana; Rina Novianty; Hartas Hasbi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
This study aims to analyze the effect of knowledge and promotion on public interest in saving for Hajj in Islamic banks. The type of research is quantitative with 97 respondents from the Muslim community in Bone Regency, using random sampling techniques and Likert scale questionnaires distributed online. Data analysis was carried out by classical assumption test, multiple linear regression, hypothesis testing, and coefficient of determination (R²) using SPSS 20. The results show: (1) Knowledge has a significant positive effect on saving interest (Tcount 2.012 > Ttabel 1.985, sig 0.000 <0.05). (2) Promotion has a significant positive effect on saving interest (Tcount 6.251> Ttabel 1.985, sig 0.000 <0.05). (3) Simultaneously, knowledge and promotion have a significant positive effect on interest in saving (Fcount 12.929 > Ftable 3.09, sig 0.000 < 0.05).